Development of Aplikasi Satu Data Kesehatan (ASDK) on key performance indicator of District Health Office of Kulon Progo using District Health Information Software 2 (DHIS2) - Sanjaya, Guardian Yoki; Prasetyawati, Dini; Pratama, Rio Aditya; Sutriana, Vivi Ninda; Lazuardi, Lutfan; Setiawan, Mohammad Yusuf; Sutaryana, Beni Mulyadi; Supriati, Titi (Journal of Community Empowerment for Health, 2024)
Introduction: Many health applications have been developed at various levels, including primary care, hospitals, district and provincial health offices, private sectors, and the national level, resulting in the fragmentation of health data at the primary health center level. Assisted by Department of Health Policy and Management, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Aplikasi Satu Data Kesehatan (ASDK) Kulon Progo, based on an open-source technology District Health Information Software 2 (DHIS2) was used to mitigate health data fragmentation in District Health Office of Kulon Progo that has been struggled since 2018 to integrate several routine health data from different programs. Methods: The activity focused on integrating routine data from the nutrition program, maternal and child health program, and immunization to create an ASDK Kulon Progo dashboard for the 2021-2022 period based on various levels. The steps taken to continue this integration into the ASDK included analyzing needs, identifying routine program data, compiling blueprint data, preparing metadata, monitoring, importing routine program data, analyzing and vizualizing it according to the needs of each program.Results: Several metadata have been established on ASDK Kulon Progo based on activities conducted from April to December 2022. These metadata include data elements and indicators featured in six health dashboards. Furthermore, various forms of data visualization, such as pivot tables, charts, and maps have been compiled and integrated into the health dashboards on ASDK Kulon Progo. Conclusion: As a system developed to support monitoring and evaluation activities, six ASDK Kulon Progo dashboards have been arranged based on integrating various health data from cross-program within the District Health Office of Kulon Progo. Support and supervision are required to sustain the implementation of ASDK Kulon Progo.